The Ritual Ukuwala Mahiate: The Integration of Tradition and Religion of the Indigenous Community of Moluccas, Indonesia - Malawat, Mahdi; Ridwan, M.; Sulaeman, Sulaeman; Darma Darma, (Technium Social Sciences Journal, 2021)
The purpose of this research is to describe the ritual Ukuwala Mahiate of the Indigenous community Moluccas, Indonesia. The Ukuwala Mahiate, an integral part of the rituals of the Indigenous community, is considered a fusion of Islamic culture’s interaction with local traditions and comprises ritual elements ranging from tools such as Nyuwelain Matehu to more complex elements. This research employed a subjective interpretive paradigm with an ethnographic qualitative approach. The study finds that the integration of tradition and religion of the Ukuwala Mahiate ritual is formed as the interpretation of the ritual processes the tradition of community and Mosque procession, Nyuwelain Matehu procession and proof, and affect the Moluccas life. The Ukuwala Mahiate is considered having deep significance, as an offering, veneration of ancestral spirits, and an act of social solidarity with a fellow of the indigenous community.